Diseased cinema : plagues, pandemics and zombies in American movies - Alpert, Robert; Eisenberg, Merle; Mordechai, Lee (Edinburgh University Press, 2024)
This volume discusses how the depiction of diseases in movies has changed over the last century and what these changes reveal about American culture.